2023
DOI: 10.1111/dar.13657
|View full text |Cite
|
Sign up to set email alerts
|

Trends in and factors associated with parental provision of alcohol to minors in Western Australia, 2013–2019

Abstract: Introduction Some parents provide alcohol to their underage children, despite a range of negative outcomes being associated with this practice. The present study aimed to assess factors associated with and changes in parental provision behaviours from 2013 to 2019 in Western Australia. Methods Annual cross‐sectional online surveys were conducted (total n = 2635). Assessed variables included parents' demographic characteristics, alcohol use, awareness of the relevant Australian alcohol guideline, attitudes to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Early evaluations have found that these campaigns are likely to influence parents’ discussion of alcohol-related issues with their child(ren), although this did not always result in a reduction of parental supply ( Johnston et al, 2018 ). However, an additional study, recently conducted in Western Australia, found a decline in parental supply of alcohol over the time period 2013–19, corresponding to the implementation of parent-targeted state-wide mass media campaigns ( Booth et al, 2023 ). Importantly, parental supply campaigns may rely on prevalence data to address parents’ perceptions of social norms (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Early evaluations have found that these campaigns are likely to influence parents’ discussion of alcohol-related issues with their child(ren), although this did not always result in a reduction of parental supply ( Johnston et al, 2018 ). However, an additional study, recently conducted in Western Australia, found a decline in parental supply of alcohol over the time period 2013–19, corresponding to the implementation of parent-targeted state-wide mass media campaigns ( Booth et al, 2023 ). Importantly, parental supply campaigns may rely on prevalence data to address parents’ perceptions of social norms (i.e.…”
Section: Discussionmentioning
confidence: 99%